DEVELOPMENT AND VALIDATION OF STABILITY INDICATING RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF LEVOSULPIRIDE - NANDAKISHORE AGARWAL,; B.JAGADEESH, (International Journal of Pharma and Bio Sciences, 2012)
A simple, economic, selective, precise, and stability-indicating Reverse phase High Performance Liquid Chromatography method for analysis of Levosulpiride and Rabeprazole sodium, was developed and validated according to ICH guidelines. The quantification of the drug was carried out using Hypersil BDS C18 250mm × 4.6mm × 5µm or its equivalent in isocratic mode, with mobile phase compressing of Buffer: Acetonitrile (72:28) the flow rate was 1.5ml/min and the detection was carried at 282 nm. The retention time for Levosulpiride and Rabeprazole sodium was found to be 2.23 and 7.27min respectively. The percent assay was found to be 99.7%. The method was also applied for the determination of Levosulpiride and Rabeprazole sodium in the presence of their degradation products formed under variety of stress conditions. Proposed method was validated for precision, accuracy, linearity range, specificity and robustness.